Practical and theoretical significance of studying the rules of international competitions in the sport of youth wrestling - A.R.Abdulaxatov. (Zien Journals, 2022)
The authors present the dynamically developing Uzbek national sport, the brand of wrestling as a national and universal value, its role in educating students in the higher education system, as well as the results of pedagogical experiments
Keywords: national and universal values; struggle; patriotism; education